Estimation of some Organophosphorus Pesticides Using Carbon Paste Electrode Coupled with Molecularly Imprinted Polymers (Baghdad Science Journal, 2018)
The aim of this study was to develop a sensor based on a carbon paste electrodes (CPEs) modified with used MIP for determination of organophosphorus pesticides (OPPs). The modified electrode exhibited a significantly increased sensitivity and selectivity of (OPPs). The MIP was prepared by thermo-polymerization method using N,N-diethylaminoethymethacrylate (NNDAA) as functional monomer, N,N-1,4-phenylenediacrylamide (NNPDA) as cross-linker, the acetonitrile used as solvent and (Opps) as the template molecule. The three OPPs (diazinon, quinalphos and chlorpyrifos) were chosen as the templates, which have been selected as base analytes which used widely in agriculture sector. The extraction efficiency of the imprinted polymers has been evaluated by various parameters affecting to optimize the selective pre-concentration of OPPs from aqueous samples. The extraction efficiency of the MIPs-OPPs from environmental water samples was evaluated using carbon paste electrode and analytical parameters of the method, the slopes, linearity and detection limits of the liquid electrodes were ranged from 24.8 – 31.3 mV/decade , (10-1 - 10-7 ) mg L-1and (2.2-8.2x10-6) mg L-1, respectively with correlation coefficient (r) (0.9991-0.9998) and repeatability were established. The method was validated and successfully applied to determined OPPs compounds from environmental water samples.